A produção teatral carioca: história, exemplos e experiências - Lima, Ana Luisa (2014)
This study aims to analyze the different management models of Rio’s theatre since 1950. There were many transformations suffered by the city’s theatrical sector, especially with the redefinition of the state’s role to a culture promoter. From the history of Brazilian theatre, the historical context and cultural policies implemented, the intention is to provide an overview of Rio’s theatrical production of the time and identify essential points at which theatrical segment is found. This paper proposes a reflection about the current practices from these changes in theatrical production processes of Rio de Janeiro city.